2020
DOI: 10.1155/2020/7194780
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Risk Assessment of Health-Related Hazardous Events in the Drinking Water Supply System from Source to Tap in Gaza Strip, Palestine

Abstract: Background. The traditional approach in the management of the quality drinking water, and relying on end-product testing, has proven ineffective in protecting public health. Therefore, the transition to a systematic approach in drinking water supply systems management from the source to the consumer tap was taken as a water safety plan (WSP). Objective. The study aims to investigate the health-related hazardous events in order to decide on the best risk-reduction strategies in the supply of drinking water in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Water and electricity shortages are common in Palestine and pre-COVID-19; it has been documented repeatedly how water and electrical power supplies were inadequate to meet Palestinian household’s needs, particularly in the Gaza Strip. 16 19 These shortages worsened current COVID-19 as most electrical engines need fuel, which was not possible due to fuel import restrictions, which also affected water pumps. Interestingly, the majority of the population uses mobile Internet bands or 12 V stable power supply for wifi router, making wifi much more accessible than potable water or electricity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and electricity shortages are common in Palestine and pre-COVID-19; it has been documented repeatedly how water and electrical power supplies were inadequate to meet Palestinian household’s needs, particularly in the Gaza Strip. 16 19 These shortages worsened current COVID-19 as most electrical engines need fuel, which was not possible due to fuel import restrictions, which also affected water pumps. Interestingly, the majority of the population uses mobile Internet bands or 12 V stable power supply for wifi router, making wifi much more accessible than potable water or electricity.…”
Section: Discussionmentioning
confidence: 99%
“…Abuzerr and his colleagues reported that water and electrical power supplies were inadequate to meet the Palestinian family’s demand. 16 19 …”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted at Al-Shifa medical complex which is located in the Gaza Strip, a setting suffering prolonged crises and experiencing persistent humanitarian situations. Difficulty accessing care, scarcities in resources, medications, insufficient health facilities, and staff capacity, tremendously challenging living circumstances, a disjointed healthcare system, and snowballing chronic diseases influence the health of people in the Gaza Strip (24)(25)(26)(27).…”
Section: Context Of the Study Settingmentioning
confidence: 99%
“…Safe drinking water supply is essential for sustaining good public health in urban residents (WHO, 2004). The traditional method of drinking water supply quality control based on end-pipe monitoring, which relies on final water quality and bacterial indicators, is inefficient and uneconomic in protecting public health by water supply systems (Abuzerr et al, 2020;Jose, 2005), as a result, the World Health Organisation (WHO) encouraged and recommended water safety plan (WSP) based on risk assessment and risk management from catchment to consumers, which states that; "The most effective means of securing the safety of a drinking water supply is through the use of a comprehensive risk assessment and risk management approach that encompasses all steps in the water supply from catchment to consumers (Figure 1), such approaches are known as water safety plan" (Bartram et al, 2009;WHO, 2004WHO, , 2011 WSP is simply a documented plan that identifies hazards; assesses risks from catchment to consumers; Prioritizes risks (with focus on highest risks) and Mitigates risks through control measures. This means moving away from reliance on output monitoring (measuring parameters in final water), and moving into input monitoring (measuring parameters which show that the system is working) (Bartram et al, 2009, Emma andPhillips, 2014).…”
Section: Introductionmentioning
confidence: 99%